The Effectiveness of Immunization - M. Faried Kaspan (Indonesian Pediatric Society, 1991)
This article reviews the expanded programme on immunization in Indonesia, Pengembangan Program lmunisasi (PPI) which was launched in 1977. We are apt to know what the current situation is after ten years have passed.WHO proposes that EPI/PPI be systemically evaluated with respect to their effectiveness which is reflected by a reduction achieved in the incidence of the target diseases. Priority is being accorded to measuring disease trends for three diseases i.e. poliomyelitis, measles and neonatal tetanus.A considerable effect on target diseases had been observed and it was evident that PPI can reduce the incidence of target diseases. A goal had been set to eliminate indigenous paralytic poliomyelitis by the end of the fifth